INSIDENSI PENYAKIT LAYU FUSARIUM PADA TANAMAN TOMAT (Lycopersicum esculentum Mill) DI KECAMATAN LANGOWAN BARAT - Muhammad Fadly Syam; Max M. Ratulangi; Guntur S.J. Manengkey; Max Tulung (Universitas Sam Ratulangi, 2014)
ABSTRACKTomato (Lycopersicum esculentum Mill) is no stranger to the community as a tomato vegetable crops play an important role in the nutrition community. This study aims to determine the cause of Fusarium wilt disease and the incidence of disease. This study was conducted in farmers' fields in the village of Tumaratas, Raringis, and Kopiwangker from February to April 2014 This study used a survey method or field observation purposive sampling. Materials and tools used in this study is the tomato crop land, plants Fusarium wilt disease, PDA, CLA media, antibiotics, distilled water, 95% alcohol, petridish, parafilm, test tube, needles ose, spirit lamp, analytical scales, tweezers, cutter, masking tape, autoclave, laminar air flow, rack culture, cover glass, glass objects, microscope, digital cameras, and stationery. The results showed the fungus that causes Fusarium wilt disease infecting tomato plants in the District of West Langowan is Fusarium sp. The incidence of Fusarium wilt disease on tomato plants in the District of West Langowan is Tumaratas village average of 6.16%, the village Raringis average of 8.66%, and the average village Kopiwangker 9.61%. The highest incidence of the disease an average of 13.66% while the lowest incidence of tomato plants with an average of 4.33%.Keywords : Tomato plant, Fusarium sp.